2019
DOI: 10.1021/acssuschemeng.9b03905
|View full text |Cite
|
Sign up to set email alerts
|

Scalable and Sustainable Total Pathogen Removal Filter Paper for Point-of-Use Drinking Water Purification in Bangladesh

Abstract: This article describes for the first time the full cycle of development from raw material cultivation to real-life application of a truly sustainable and scalable filter paper material intended for point-of-use drinking water purification in Bangladesh. The filter paper, featuring tailored pathogen removal properties, is produced from nanocellulose extracted from Pithophora green macroalgae, growing locally in Bangladesh, a new unexploited resource that can address a global problem. We demonstrate that the Pit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…A team of researchers in Bangladesh developed a Pithophora sp. based sustainable and scalable filter paper for point-of-use purification of drinking water [ 115 ]. All types of infectious viruses and bacteria were demonstrated to be removed from the water by Pithophora cellulose filter paper.…”
Section: Microalgae-based Approaches; An Underexplored Biological Trementioning
confidence: 99%
“…A team of researchers in Bangladesh developed a Pithophora sp. based sustainable and scalable filter paper for point-of-use purification of drinking water [ 115 ]. All types of infectious viruses and bacteria were demonstrated to be removed from the water by Pithophora cellulose filter paper.…”
Section: Microalgae-based Approaches; An Underexplored Biological Trementioning
confidence: 99%
“…Recently, cellulose nanofibers (CNFs) have received a great deal of attention in a wide variety of applications such as reinforcement in nanocomposites, biomaterials, paper, packaging, electronic devices, and filtration membranes. This is owing to their unique properties such as low density, low thermal expansion, superior mechanical properties, biodegradability, biocompatibility, and a large surface-to-volume ratio. , Commonly, a series of chemical treatments is a prerequisite for the removal of lignin and hemicellulose from lignocellulosic materials before disintegration. ,, For example, the well-known combination of acidified sodium chlorite (NaClO 2 ) and alkaline has long been used to treat lignocellulosic materials such as wood, rice straw, potatoes, kenaf, and agricultural residues . With its long processing time and high chemical and energy consumption, this chemical purification process is very expensive .…”
Section: Introductionmentioning
confidence: 99%
“…Although coarse filters from cellulose fibers are commonplace, recent examples of nanocellulose membranes have shown that the narrow pore size of the membranes can effectively remove both bacteria and viruses from drinking water. 34 Although these filters have shown great promise in a wide range of applications, limiting factors are the high opposing pressures and costly procedures that are required to retain CNFs during the formation of nanocellulose networks. As a result, it would be advantageous to rapidly produce nanocellulose membranes, capable of filtering sub-micron particles, using low cost, standard filter papers as a base structure.…”
Section: Introductionmentioning
confidence: 99%
“…Cellulose-rich fibers and papers made thereof have long been used as filters to remove both airborne and waterborne contaminants. Recently, nanocelluloses have been utilized in a variety of water remediation and separation applications both as adsorbents and membranes. Ion remediation utilizes the high specific surface area of nanocelluloses and the specific chemistry on the cellulose surface to bind mobile ions. Comparatively, particle filtration relies on size exclusion to remove particles such as debris and pathogens.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation